Relationship Between Cognitive Dysfunction (MoCA-INA Score) with Disease Activity, Erythrocyte Sedimentation Rate, and C-Reactive Protein in Systemic Lupus Erythematosus Patients : Relationship Between Cognitive Dysfunction (MoCA-INA Score) with Disease Activity, Erythrocyte Sedimentation Rate, and C-Reactive Protein in Systemic Lupus Erythematosus Patients - Bantar Sutoko; Suyanto Hadi; Elfian Rachmawati; Suharyo Hadisaputro; Handono Kalim (Medica Hospitalia : Journal of Clinical Medicine, 2022)
BACKGROUND: Neuropsychiatric Systemic Lupus Erythematosus (NPSLE) is one of the clinical manifestations affecting the brain in SLE, which the most frequent condition was cognitive dysfunction (CD). CD has a negative impact on the quality of life of SLE patients and causes impaired social function and reduced work productivity. Previous studies regarding correlation between cognitive dysfunction with disease activity, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) showed various results. AIM: The purpose of this study was to assess the correlation of CD using MoCA- INA score with disease activity (SLEDAI-2K score), ESR and CRP in SLE patients. METHODS: A cross-sectional study design was applied in this research. The subjects of this research were SLE patients measured by MoCA-INA score, SLEDAI-2K score, ESR, and CRP. Spearman rank correlation test was applied in this study to assess the relationship of the variables. RESULT: The study subjects consisted of 53 women diagnosed with SLE with an average age of 34 years old. 49.1 % of the subjects had high school education background. There was a moderate significant correlation between MoCA-INA score and ESR (r= -0.408, p=0.002) and also to CRP (r= -0.314 p=0.022). There was no significant correlation of disease activity and MoCA-INA score (r = -0.086 p = 0.539). CONCLUSION: The low levels of ESR and CRP were associated with CD in SLE patients. KEYWORDS: cognitive dysfunction, c-reactive protein, disease activity, erythrocyte sedimentation rate, systemic lupus erythematosus.